A scientific assessment of the validity of mystical experiences : understanding altered psychological and neurophysiological states - Papanicolaou, Andrew C. (New York, NY : Routledge, 2021)
"In this book the approach of the natural sciences is adopted to confront the ontological question of how far mystical experiences can be considered as reports of an objective reality rather than reports of subjective delusions. Moving beyond traditional philosophical or cultural and theological interpretations of mystical phenomena, the author uses inductive inference to analyze claims made by secular and religious mystics, highlight links between altered states of consciousness and neurochemistry, and counters reductionist claims that mystical states are exclusively products of neurochemical, neurophysiological, or psychopathological factors. The text also considers the positive long-term effects of proper use of psychedelics and meditation. This fresh approach to mystical experiences will be of interest to scholars, researchers, and postgraduate students working in the areas of psychology and neuroscience, and with an interest in mysticism in religious studies and philosophy"--
Defining mystical states and experiences -- Unintentional and deliberate methods of attaining mystical states : religious, cultural, and philosophical perspectives -- Mystical states achieved through psychedelics: the origins, classical, and contemporary use of psychedelics -- Questioning the reliability of mystical states : identifying features -- Questioning the validity of mystical states : opinions and objections -- The experiencing subject and mystical object : defining validity of the mystical state.
OCLC-licensed vendor bibliographic record.
Keywords: Altered states of consciousness; Mysticism; PSYCHOLOGY / Social Psychology; PSYCHOLOGY / Neuropsychology; PSYCHOLOGY / Movements / Transpersonal